Associations Between Neurochemistry and Gait Performance Following Concussion in Collegiate Athletes. Issue 5 (September 2020) - Charney, Molly F.; Howell, David R.; Lanois, Corey; Starr, Tyler C.; Liao, Huijun; Coello, Eduardo; Breedlove, Katherine M.; Meehan, William P.; Koerte, Inga; Lin, Alexander P.
Abstract : Objective: To evaluate the strength of associations between single-task and dual-task gait measures and posterior cingulate gyrus (PCG) neurochemicals in acutely concussed collegiate athletes. Setting: Participants were recruited from an NCAA Division 1 University. Participants: Nineteen collegiate athletes acutely (<4 days) following sports-related concussion. Design: We acquired magnetic resonance spectroscopy (MRS) in the PCG and gait performance measurements in the participants, acutely following concussion. Linear mixed-effects models were constructed to measure the effect of gait performance, in the single- and dual-task settings, and sex on the 6 neurochemicals quantified with MRS in mmol. Correlation coefficients were also calculated to determine the direction and strength of the relationship between MRS neurochemicals and gait performance, postconcussion symptom score, and number of previous concussions. Main Measures: Average gait speed, average cadence, N -acetyl aspartate, choline, myo-inositol, glutathione, glutamate plus glutamine, and creatine. Results: Single-task gait speed ( P = .0056) and cadence ( P = .0065) had significant effects on myo-inositol concentrations in the PCG, independent of sex, in concussed collegiate athletes. Single-task cadence ( P = .047) also had a significant effect on glutathione in the PCG. No significant effects were observed between dual-task gait performance and PCG neurochemistry. Conclusions: These findings indicate that increased concentrations of neuroinflammatory markers in the PCG are associated with slower single-task gait performance within 4 days of sports-related concussion.